Jejaring Kemitraan Dalam Pemahaman Pengelola Lembaga Pendidikan Non-Formal - Suryawahyuni Latief; Santi Hendrayani2; Samsuddin (STIT Muhammadiyah Paciran Lamongan, 2022)
PKBM as non-formal education provider in the form of equality education and life skills cannot stand alone to carry out its duties and roles. Therefore PKBM builds partnership networks with other parties so that roles and functions can be achieved, given the limited resources owned by PKBM units. The purpose of this study is to describe how the understanding of PKBM unit managers in building partnership networks. To answer the research objectives in general, the researcher explores information regarding the meaning of partnership networks for PKBM unit managers, characteristics of partnership networks, and factors that become obstacles in building partnership networks.This study uses a qualitative descriptive research method, involving 15 PKBM unit managers from several districts in Jambi Province, namely Batanghari, Merangin and Muaro Bungo. Data collected through observation, interviews, and documents were analyzed by following the steps of data analysis in qualitative research. The data that has been analyzed is tested for its validity in theory, field sources, and other sources.This study found that the understanding of building a partnership network for PKBM unit managers was limited to a practical understanding so that the available service programs could run according to plan with the limited resources of the PKBM unit. Therefore, this needs to be addressed by providing direct experience to PKBM unit managers through visits to other PKBM units that serve as references and providing training regarding PKBM management. The results of this study can be used for the development of community-based educational organizations.